Rapid weight loss decreases serum Testosterone - Karila, T. A. M.; Sarkkinen, P.; Marttinen, M.; Seppälä, T.; Mero, A.; Tallroth, K. (International Journal of Sports Medicine, 2008)
To investigate the effects of a rapid weight reduction program under authentic pre-competition conditions, eighteen elite wrestlers were studied with dual-energy X-ray absorptiometry (DXA) before and after two to three weeks' weight reduction regimens. In order to establish the degree of dehydration and hormonal status, blood samples were collected to obtain blood chemistry, electrolytes and endocrinological parameters after both DXA measurements. The mean weight loss was 8.2 ± 2.3 % and it was constituted by the mean reductions of fat mass of 16 ± 6.9 % (p = 0.001) and lean body mass of 7.9 ± 2.5 %. The rapid weight reduction caused significant dehydration which was noticed as increased blood hemoglobin (7.8 ± 5.9 %, p = 0.001), hematocrit (11.3 ± 6.8 %, p = 0.001), and serum creatinine (35 ± 23 %, p = 0.001). There was a significant decrease in serum testosterone (63 ± 33 %, p = 0.001) and luteinizing hormone (54 ± 47 %, p = 0.001) concentrations. A reduced body weight correlated with decreased serum testosterone concentration (r = 0.53, p = 0.024). Serum sex hormone binding globulin concentration increased significantly (40 ± 21 %, p = 0.001). The results suggest that even short-term weight reduction may have marked effects on body composition, blood chemistry and hormonal parameters. It may constitute a possible health risk at least in a growing adolescent athlete.